Inovasi Pengembangan Budidaya Ayam Petelur untuk Ketahanan Pangan dan Penanganan Fenomena Stunting Melalui Instrumen Zakat Produktif Pada Masyarakat Daerah Tertinggal Pasca Covid-19 - Efendi, Sulhan; Gumilang, Dimas; Razzaaq, Noor Khafid; Rajendra, Muhammad Raditya (Diponegoro Journal of Islamic Economics and Business, 2021)
The Central Statistics Agency in their report in 2020 reported that in the first quarter of 2020, Indonesian economy was only able to growth by 2.97% from the previously projected in the level of 4.6%. The failure to achieve the projection indicates that Indonesia is in danger of economic crisis. On the other hand, Indonesia turned out to be a middle to upperlevel country in terms of income. This condition is recored in the World Bank report which stated that Indonesia’s gross national income per capita is 4,050 dollars per year in 2019. Nevertheless, Indonesia still has some homeworks especially in terms of food security and also adequate nutrition of people. The Global Nutrition Report notes that Indonesia is one of three countries that have problem with this physical condition in children (stunting). To deal with this problem, this article formuate a solution to propose productive zakat instrument as an innovation to the development of laying hens cultivation to improve food security and nutrition of people in underdeveloped region.